Իսուվայի կրոնական կենտրոնները խեթական դարաշրջանում - Քոսյան, Արամ («Զանգակ - 97»)
The paper deals with two prominent political entities of Isuwa (later Arm. Tsopk) - Watarusna and Sullama which, according to the Hittite cuneifomi texts, were also outstanding religious centers of the area. Two Hittite texts - KUB LVI 40 and КВо XXXI 169 describe yearly and occasional offerings to the deities of these cities, i. e. the god of Watarusna and the Storm-god Sullama. Füll publication of these texts adds a reliable data dealing with the cult of these deities. KUB LVI 40 contains also scveral place-names, probably located within the kingdom of Isuwa in the XIIIc. B. C.
Keywords: Պատմություն; Կրոն